Language and understanding of cardiopulmonary resuscitation amongst an aged inpatient population. Issue 2 (7th February 2017) - Levinson, M.; Ho, S.; Mills, A.; Kelly, B.; Gellie, A.; Rouse, A.
Abstract: Greater patient involvement in health decision-making requires exchange of information between the patient and the healthcare professionals. Decisions regarding healthcare at the end of life include consideration of cardiopulmonary resuscitation (CPR). The stated objectives of this study were to determine how often language around concepts of resuscitation is used in the community by examination of the English language corpora (ELC); to explore the understanding of the same language by a group of older hospital patients; and to determine the patients' knowledge of the process and success of CPR, as well as the sources of their information. Medical inpatients aged 75 years and older were surveyed to this end in the setting of a tertiary university teaching hospital. Interrogation of the Australian, British and American English Corpora was accomplished by a linguist, and a questionnaire and semi-structured interview were administered to ascertain patient knowledge. We demonstrated that although medical inpatients have some familiarity with terms relating to resuscitation, there is a lack of understanding of the context, process and outcomes of CPR. The predominant sources of information were television and print media. Examination of the ELC revealed a paucity of the use of terms related to resuscitation. This finding indicates that physicians have a duty of care to determine patients' understanding around resuscitation language, and terms used, in discussions of their preferences before assuming their engagement in shared decision-making. More open public discussion around death and resuscitation would increase the general knowledge of the population and would provide a better foundation for the discussions in times of need.